Vitamin D regulates the production of vascular endothelial growth factor: A triggering cause in the pathogenesis of rheumatic heart disease?. (October 2016) - Sarkar, Subendu; Chopra, Seema; Rohit, Manoj Kumar; Banerjee, Dibyajyoti; Chakraborti, Anuradha
Abstract: Rheumatic heart disease (RHD) remains a major cause of cardiac related mortality and morbidity in the developing countries due to poor diagnosis and lack of proper therapeutics. The definite reason of heart valve injury during RHD is poorly understood. Valvular endothelial cells play an important role in pathogenesis of different cardiovascular diseases. Besides, the regulation of vitamin D (calciferol) and VEGF (vascular endothelial growth factor) results in the functional changes in endothelial cells. However, the crosstalk between vitamin D and VEGF in the pathogenesis of RHD is not yet unfurled. Evidences in the concerned fields are documented by searching through Google Scholar and Pubmed. Literature based survey has revealed that vascular endothelium, especially endothelial cells play important roles in valvular remodelling during cardiovascular diseases. Endothelial cell dysfunction leads to heart valve remodelling, which furthermore initiates the pathogenesis of valvular heart disease. Vitamin D has the potential to maintain the concentration of VEGF in the circulation and induce the function of endothelial cells. Hence, we hypothesize that vitamin D and VEGF homeostasis can alter the function of endothelial cells, which may subsequently trigger the valvular remodelling or even damage of heart valves during the progression of RHD pathogenesis. Our hypothesis shed light on the evidence based knowledge translation of plausible cellular phenomena due to vitamin D/VEGF homeostasis during valvular vandalism in RHD.